2019
DOI: 10.20944/preprints201910.0331.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Killer Immunoglobulin-Like Receptor 2DL4 (CD158d) Regulates Human Mast Cells Both Positively and Negatively: Possible Roles in Pregnancy and Cancer Metastasis

Abstract: Killer immunoglobulin-like receptor (KIR) 2DL4 (CD158d) was previously thought to be a human NK-cell-specific protein but its expression has also been demonstrated in human mast cells. Mast cells are involved in allergic reactions via their KIT-mediated and IgE receptor-mediated responses. We recently detected the expression of KIR2DL4 in human cultured mast cells established from peripheral blood derived from healthy volunteers (PB-mast), a human mast cell line (LAD2), and non-neoplastic mast cells, including… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Mast cells have the ability to facilitate tumor proliferation and invasion directly,and indirectly promote tumor proliferation and invasion by regulating tumor microenvironment [22], it may provide further evidence for Mast cells can be applied in the adjuvant treatment of mammary adenocarcinoma and melanoma [23]. Previous studies have shown that Th2 cells, T helper cells, and Mast cells may play key roles in the development and invasion of cancer [24][25][26][27], our studies show that these immune cells may play a role in gastric cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Mast cells have the ability to facilitate tumor proliferation and invasion directly,and indirectly promote tumor proliferation and invasion by regulating tumor microenvironment [22], it may provide further evidence for Mast cells can be applied in the adjuvant treatment of mammary adenocarcinoma and melanoma [23]. Previous studies have shown that Th2 cells, T helper cells, and Mast cells may play key roles in the development and invasion of cancer [24][25][26][27], our studies show that these immune cells may play a role in gastric cancer.…”
Section: Discussionmentioning
confidence: 98%
“…The possible participation in the initiation of pregnancy has been linked with the presence of the KIR2DL4 receptor. However, it is not conclusive as positive and no-effect studies can be found in the literature [ 89 , 90 ]. A recent meta-analysis of data from articles from the databases like Web of Science, PubMed, Scopus, Google Scholar, etc.…”
Section: Kir/hla Interaction In Pregnancy Complicationmentioning
confidence: 99%
“…Tumor cells could escape immune surveillance by induction of KLRK1 ligand expression [30]. KIR2DL4 belongs to the killer cell immunoglobulin-like receptors, transmembrane glycoproteins expressed on the surface of NK cells and some subsets of T cells [31]. IL18RAP, an accessory subunit of the IL-18 receptor, can enhance IL-18-binding activity and is involved in IL-18-dependent signal transduction, leading to the activation of NF-κB and JNK pathways [32].…”
Section: Discussionmentioning
confidence: 99%